Firm financing and public support measures during the pandemic - Ida Rommedahl Julin; Andreas Kuchler; Alexander Meldgaard Otte (Danmarks Nationalbank, 2021)
This paper studies Danish non-financial firms' debt financing decisions during covid-19 with a focus on the impact of government support measures. The growth in credit from banks and mortgage banks to firms has been modest during the pandemic, and many firms reduced their debt level in the initial phases. Firms that were more exposed to the pandemic had higher debt growth than other firms. That was in particular the case for those with weaker pre-pandemic balance sheets. Public liquidity measures such as deferred tax and VAT payments served as a substitute for more traditional debt funding sources during the pandemic. There are indications that firms that were weaker even before the pandemic have received a disproportionately high share of tax and VAT loans. These results suggest that there may be substantial costs and risks associated with such support measures. We find no differences in debt developments between firms receiving and those not receiving benefits from the wage and fixed cost compensation schemes.
Keywords: E61; E65; G21; G28; G30; H12; H32; 330; Economic activity and employment; public financesand fiscal policy; financial assets and balances